Application of Mesenchymal Stem Cell-Derived Schwann Cell-like Cells Spared Neuromuscular Junctions and Enhanced Functional Recovery After Peripheral Nerve Injury - Yu Hwa Nam; Ji-Sup Kim; Yoonji Yum; Juhee Yoon; Hyeryung Song; Ho-Jin Kim; Jaeseung Lim; Saeyoung Park; Sung-Chul Jung (Cells)
In general, the nerve cells of the peripheral nervous system regenerate normally within a certain period after the physical damage of their axon. However, when peripheral nerves are transected by trauma or tissue extraction for cancer treatment, spontaneous nerve regeneration cannot occur. Therefore, it is necessary to perform microsurgery to connect the transected nerve directly or insert a nerve conduit to connect it. In this study, we applied human tonsillar mesenchymal stem cell (TMSC)-derived Schwann cell-like cells (TMSC-SCs) to facilitate nerve regeneration and prevent muscle atrophy after neurorrhaphy. The TMSC-SCs were manufactured in a good manufacturing practice facility and termed neuronal regeneration-promoting cells (NRPCs). A rat model of peripheral nerve injury (PNI) was generated and a mixture of NRPCs and fibrin glue was transplanted into the injured nerve after neurorrhaphy. The application of NRPCs and fibrin glue led to the efficient induction of sciatic nerve regeneration, with the sparing of gastrocnemius muscles and neuromuscular junctions. This sparing effect of NRPCs toward neuromuscular junctions might prevent muscle atrophy after neurorrhaphy. These results suggest that a mixture of NRPCs and fibrin glue may be a therapeutic candidate to enable peripheral nerve and muscle regeneration in the context of neurorrhaphy in patients with PNI.